Efficient suppression of endogenous CFTR nonsense mutations using anticodon-engineered transfer RNAs - Wooree Ko; Joseph J. Porter; Matthew T. Sipple; Katherine M. Edwards; John D. Lueck (Elsevier, 2022)
Nonsense mutations or premature termination codons (PTCs) comprise ∼11% of all genetic lesions, which result in over 7,000 distinct genetic diseases. Due to their outsized impact on human health, considerable effort has been made to find therapies for nonsense-associated diseases. Suppressor tRNAs have long been identified as a possible therapeutic for nonsense-associated diseases; however, their ability to inhibit nonsense-mediated mRNA decay (NMD) and support significant protein translation from endogenous transcripts has not been determined in mammalian cells. Here, we investigated the ability of anticodon edited (ACE)-tRNAs to suppress cystic fibrosis (CF) causing PTCs in the cystic fibrosis transmembrane regulator (CFTR) gene in gene-edited immortalized human bronchial epithelial (16HBEge) cells. Delivery of ACE-tRNAs to 16HBEge cells harboring three common CF mutations G542XUGA-, R1162XUGA-, and W1282XUGA-CFTR PTCs significantly inhibited NMD and rescued endogenous mRNA expression. Furthermore, delivery of our highly active leucine-encoding ACE-tRNA resulted in rescue of W1282X-CFTR channel function to levels that significantly exceed the necessary CFTR channel function for therapeutic relevance. This study establishes the ACE-tRNA approach as a potential standalone therapeutic for nonsense-associated diseases due to its ability to rescue both mRNA and full-length protein expression from PTC-containing endogenous genes.